2016
DOI: 10.1136/annrheumdis-2016-210104
|View full text |Cite
|
Sign up to set email alerts
|

Filgotinib (GLPG0634/GS-6034), an oral JAK1 selective inhibitor, is effective in combination with methotrexate (MTX) in patients with active rheumatoid arthritis and insufficient response to MTX: results from a randomised, dose-finding study (DARWIN 1)

Abstract: ObjectivesTo evaluate the efficacy and safety of different doses and regimens of filgotinib, an oral Janus kinase 1 inhibitor, as add-on treatment to methotrexate (MTX) in patients with active rheumatoid arthritis (RA) and inadequate response to MTX.MethodsIn this 24-week phase IIb study, patients with moderate-to-severe active RA receiving a stable dose of MTX were randomised (1:1:1:1:1:1:1) to receive placebo or 50, 100 or 200 mg filgotinib, administered once daily or twice daily. Primary end point was the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
154
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(178 citation statements)
references
References 18 publications
7
154
1
4
Order By: Relevance
“…Clinical efficacy was observed at daily doses of 75–300 mg in a phase IIa study in patients with RA with an insufficient response to methotrexate and naïve to biological disease‐modifying anti‐rheumatic drugs, with similar effects noted for these doses in terms of improvements in C‐reactive protein and disease activity scores based on 28 joints . Subsequently, efficacy was confirmed in larger, phase IIb studies of filgotinib given as monotherapy and in combination with methotrexate . Filgotinib dosed at 100–200 mg once daily is currently being evaluated in pivotal phase III studies in patients across several indications, including RA, CD and ulcerative colitis.…”
Section: Discussionmentioning
confidence: 89%
“…Clinical efficacy was observed at daily doses of 75–300 mg in a phase IIa study in patients with RA with an insufficient response to methotrexate and naïve to biological disease‐modifying anti‐rheumatic drugs, with similar effects noted for these doses in terms of improvements in C‐reactive protein and disease activity scores based on 28 joints . Subsequently, efficacy was confirmed in larger, phase IIb studies of filgotinib given as monotherapy and in combination with methotrexate . Filgotinib dosed at 100–200 mg once daily is currently being evaluated in pivotal phase III studies in patients across several indications, including RA, CD and ulcerative colitis.…”
Section: Discussionmentioning
confidence: 89%
“…Finally, given the different JAK targets being inhibited, it can be hypothesized that the combination of baricitinib plus LFN might be of clinical interest considering that LFN inhibits JAK3 and this may explain also the additive effect of LFN when used in combination with MTX . The same should occur with Upadacitinib and Filgotinib . When examining the side effects associated to JAK inhibitors, the major one is represented by the occurrence of Herpes Zoster infection .…”
Section: Jak Inhibitors and Mtxmentioning
confidence: 99%
“…43 The same should occur with Upadacitinib and Filgotinib. 44,45 When examining the side effects associated to JAK inhibitors, the major one is represented by the occurrence of Herpes Zoster infection. 46 Despite discordant results have been described in the literature, 47 yet most recent data suggest that Zoster infection may be a side effect of MTX therapy.…”
Section: Jak Inhibitors and Mtxmentioning
confidence: 99%
“…31 In a phase 2B clinical trial in rheumatoid arthritis, filgotinib showed a dose-dependent response in combination with methotrexate. 32 …”
Section: Tofacitinib: a Pan Jak Inhibitormentioning
confidence: 99%